An IS perspective on managing change in a university - Johnston, Kevin Allan (Department of Information Systems, 2014)
This thesis aimed firstly to explore what is happening with respect to change in a South African university, and how this change affects those involved, viewed from an IS standpoint. The focus is on determining the essence and nature of organisational change in its usual situation.